DAMPAK PRIVATISASI BUMN BAGI MASYARAKAT EKONOMI DI INDONESIA - Kristianto, Djoko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT Government Indonesia found BUMN with two especial target, that is target having the character of public spirited target and economics. In target having the character of economics, BUMN meant to manage strategic business sector in order not to be mastered certain side. Target of public spirited BUMN for example can be reached to through creation of employment and also strive to awaken local economics. creation of Employment reached to through recruitment of labour by BUMN With the nun of time, privatisasi execution that happened till now still impress is intricate, long draw out, and is not transparent. Told intricate for no clear order him about privatisasi procedure and procedure. Process privatisasi from each every BUMN conducted with different treatment and procedure. Privatisasi execution also impress long draw out. Decision which have been taken government cannot is immediately executed, because various reason. This handing out is meant to analyse in order to searching BUMN privatisasi form capable to deliver benefit to Indonesia society and government, and also look for privatisasi strategy which can be accepted by various side, which is related to BUMN. Keywords : Economic Society, privatisasi BUMN.